2014
DOI: 10.1103/physreve.89.042204
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional discrete element modeling of triggered slip in sheared granular media

Abstract: This paper reports results of a three-dimensional discrete element method modeling investigation of the role of boundary vibration in perturbing stick-slip dynamics in a sheared granular layer. The focus is on the influence of vibration within a range of amplitudes and on the fact that above a threshold early slip will be induced. We study the effects of triggering beyond the vibration interval and their origins. A series of perturbed simulations are performed for 30 large slip events selected from different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 60 publications
4
51
0
Order By: Relevance
“…In the context of granular earth materials, an important example of phenomena observed in nature and in simulations, and captured in the present STZ model, is the dynamic triggering of catastrophic events [10,11,19,49], known to occur in the presence of a granular gouge layer. Specifically, we found that vibrations reduce the shear strength and clock-advance the first slip event upon loading.…”
Section: Discussionmentioning
confidence: 97%
“…In the context of granular earth materials, an important example of phenomena observed in nature and in simulations, and captured in the present STZ model, is the dynamic triggering of catastrophic events [10,11,19,49], known to occur in the presence of a granular gouge layer. Specifically, we found that vibrations reduce the shear strength and clock-advance the first slip event upon loading.…”
Section: Discussionmentioning
confidence: 97%
“…As mentioned before, the nonlinear Hertzian contact model for the particle interaction force is applied in the normal direction, and the tangential contact force is limited using the Coulomb friction law. The interparticle friction coefficient equals 0.1, which is somewhat smaller than that generally used in the literature for numerical simulations and material used in experiments [ Griffa et al ., ; Ferdowsi et al ., ; Scuderi et al ., ], but allows for larger slip events and reduces the frequency of small fluctuations in macroscopic friction signal [ Ferdowsi , ]. The employed friction coefficient is the same for dry and saturated models and therefore does not play a role in the comparison between dry and saturated models.…”
Section: Numerical Setupmentioning
confidence: 99%
“…The nature of stress accommodation and the dynamics of the stick‐slip events have been well studied in laboratory experiments and numerical simulations primarily on dry granular fault gouge [ Marone , , ; Morgan , ; Mair et al ., ; Guo and Morgan , ; Anthony and Marone , ; Johnson and Jia , ; Mair and Hazzard , ; Johnson et al ., ; Samuelson et al ., ; Johnson et al ., ; Johnson et al ., ]. Recent 3‐D discrete element method (DEM) numerical simulations of dry granular fault gouge demonstrate both spontaneous and triggered stick‐slip [ Ferdowsi et al ., ; Griffa et al ., ; Ferdowsi et al ., , ] similar to experiments. There exist a few studies of fluid‐saturated granular fault gouge as well.…”
Section: Introductionmentioning
confidence: 99%
“…Nasuno et al [] have shown that in a sheared granular material, grain‐scale rearrangements occur preceding slip. DEM simulations by Ferdowsi et al [] and Ferdowsi et al [] show that grain movement occurs at the time of, and following, slip. The observation that such local, irreversible rearrangement of grains accounts for plastic deformation and slip in a granular layer is the fundamental idea behind the Shear‐Transformation‐Zone (STZ) theory of dense granular flow—a physics‐based model to describe flow and deformation in discrete particulate media.…”
Section: Introductionmentioning
confidence: 99%